Adipocyte Oncostatin Receptor Regulates Adipose Tissue Homeostasis and Inflammation - Sanchez-Infantes, David; Stephens, Jacqueline M. (Frontiers in Immunology, 2021)
Adipocytes are the largest cell type in terms of volume, but not number, in adipose tissue. Adipocytes are prominent contributors to systemic metabolic health. Obesity, defined by excess adipose tissue (AT), is recognized as a low-grade chronic inflammatory state. Cytokines are inflammatory mediators that are produced in adipose tissue (AT) and function in both AT homeostatic as well as pathological conditions. AT inflammation is associated with systemic metabolic dysfunction and obesity-associated infiltration and proliferation of immune cells occurs in a variety of fat depots in mice and humans. AT immune cells secrete a variety of chemokines and cytokines that act in a paracrine manner on adjacent adipocytes. TNFα, IL-6, and MCP-1, are well studied mediators of AT inflammation. Oncostatin M (OSM) is another proinflammatory cytokine that is elevated in AT in human obesity, and its specific receptor (OSMRβ) is also induced in conditions of obesity and insulin resistance. OSM production and paracrine signaling in AT regulates adipogenesis and the functions of AT. This review summarizes the roles of the oncostatin M receptor (OSMRβ) as a modulator of adipocyte development and function its contributions to immunological adaptations in AT in metabolic disease states.